Battery Charging Optimization of Solar Energy based Telecom Sites in India - Dhaked, D. K.; Gopal, Y.; Birla, D. (Engineering, Technology & Applied Science Research, 2019)
Telecom sites get the power normally from the grid. At the occurrence of power outages power need to be supplied for telecom sites. The battery bank is a good option for telecom sites to fulfil power demand. This paper discusses a smooth battery bank charging and discharging system with solar power as the input supply source. The system requires a large capital investment, but it provides uninterrupted emergency power when needed. Maintaining battery banks is essential for getting optimum performance. This paper also discusses the power requirements for telecom sites backup and various parameter impacts on battery life. Methods are derived to optimize charging management of batteries in order to get maximum lifespan in addition to better battery performance throughout its useful life.